Implementation of Non-Cash Transactions in Regional Financial Management at the Regional Financial and Asset Management Agency of Central Maluku Regency - Valentina Latumahina; Christina Sososutiksno; Ferry H. Basuki (Daengku: Journal of Humanities and Social Sciences Innovation, 2024)
This study aims to examine the implementation of non-cash transactions in regional financial management at the Regional Finance and Asset Management Agency of Central Maluku Regency. The main informants used in this study were 4 people and 2 supporting informants. The analysis method used is the Quantitative Method. The results showed that communication indicators, informants about the implementation of non-cash transactions in the Regional Finance and Asset Management Agency of Central Maluku Regency, most employees in the finance department already understand the application of non-cash transactions. Human resource indicators have been used effectively, but still need to be improved, especially with regard to human resources. Indicators in the position of the application of non-cash transactions at the Regional Financial and Asset Management Agency of Central Maluku Regency show that the Treasurer must have more expertise and skills in carrying out its duties and functions. Indicators of bureaucratic structure are quite good. This is because there is a policy that regulates non-cash transactions and can be used as a standard to carry out non-cash transactions at the Regional Finance and Asset Management Agency of Central Maluku Regency.